2022
DOI: 10.3748/wjg.v28.i8.825
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA methylation analysis of SUMF2, ADAMTS5, and PXDN provides novel insights into colorectal cancer prognosis prediction in Taiwan

Abstract: BACKGROUND Patients with colorectal cancer (CRC) undergo surgery, as well as perioperative chemoradiation or adjuvant chemotherapy primarily based on the tumor–node– metastasis (TNM) cancer staging system. However, treatment responses and prognostic outcomes of patients within the same stage vary markedly. The potential use of novel biomarkers can improve prognostication and shared decision making before implementation into certain therapies. AIM To investigate whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…This study is also the first to analyze the effect of the PXDN methylation level on prognosis and report that hypermethylation of PXDN tends to represent longer patient survival times. As some studies have found that the PXDN methylation level is significant in pancreatic cancer ( 22 ) and colorectal tumors ( 23 ), we thus believe that the PXDN methylation level can be used as an independent predictor of tumor.…”
Section: Discussionmentioning
confidence: 81%
“…This study is also the first to analyze the effect of the PXDN methylation level on prognosis and report that hypermethylation of PXDN tends to represent longer patient survival times. As some studies have found that the PXDN methylation level is significant in pancreatic cancer ( 22 ) and colorectal tumors ( 23 ), we thus believe that the PXDN methylation level can be used as an independent predictor of tumor.…”
Section: Discussionmentioning
confidence: 81%
“…Genomic DNA samples were isolated from pathological tissue of CRC and adjacent normal tissue, and DNA bisulfite modification was performed according to the manufacturer’s instruction manual per a method described in a previous study [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…The total volume of the reaction solution was 20 μL; the solution contained 9 μL of HotStart Taq Premix (RBC Bioscience, Taipei, Taiwan), 9 μL of pure water, 0.5 μL of 10 μM forward and reverse primers, and 1 μL of 10 μM bisulfite-modified DNA. The PCR cycling protocol reported in our previous study was adopted for MS-PCR [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low density lipoprotein receptor-related protein 1-mediated endocytosis regulates extracellular activity of ADAMTS-5 in articular cartilage (Yamamoto et al, 2013(Yamamoto et al, , 2014. There are CpG islands within ADAMTS-5 promoter and DNA hypermethylation in ADAMTS-5 promoter is reportedly associated with increased invasiveness and poor survival in patients with colorectal cancer (Y. H. Kim et al, 2011;Li et al, 2018;Su et al, 2022). However, thus far there have been no reports concerning DNA methylation status in ADAMTS-5 promoter during OA development.…”
Section: Introductionmentioning
confidence: 99%